Place et fonctions de la patrimonialisation de la nature dans les espaces protégés. Enseignements à partir du massif de l’uKhahlamba-Drakensberg, Afrique du Sud. - Mélanie Duval (VertigO)
The aims of this article are to analyse the links between the establishment of natural protected areas and the patrimonialization of the nature. This research is based on fieldtrips done in the uKhahlamba-Drakensberg mountain range, situated on the border of South Africa and Lesotho. As several protected areas have been created throughout the 20th century, this mountain ranger is an appropriate field case to understand the social values on which natural protected areas are based and the place of patrimonialization within them. Moreover the post-colonial context leads us to analyse the question of heritage authority. As the heritage processes have been enlarged with the end of the Apartheid system, included disadvantaged people in the civil society concerned by heritage question, this case of study allows to observe if and how the way of patrimonialization of the nature has changed. This analysis underlines the evolution of the values behind nature’s patrimonialization as well as their complexity. Finally, this approach leads us to consider the durability of nature’s patrimonialization which depends on the stakeholder’s capacity to propose a holistic approach of man-environment system.